Prentice G. Downes (1909-1959) - Cockburn, Robert H. (ARCTIC, 1982)
Prentice G. Downes was one of the most singular men to travel in the North in the last years before the 1939-45 War. An able man in the wilderness and a gifted cartographer, ethnologist, and naturalist, he is best remembered as the author of Sleeping Island: The Story of One Man's Travels in the Great Barren Lands of the Canadian North, a classic of northern canoe travel. . In a letter to George Douglas in 1943, Downes remarked that his having read Napolean Comeau's Life and Sport on the North Shore of the St. Lawrence "had a great deal to do with my ever going north, as I was so interested that I set off for the North Shore to find the old gentleman." Comeau had died, but thus in 1935 Downes commenced his northern travels. In 1936 he took passage aboard R.M.S. Nascopie from Montreal to Churchill, during which trip he made copious notes on climate, geography, wildlife, Ungava Eskimo vocabulary, and northern society. From Churchill he flew to Pelican Narrows and with an Indian companion canoed to Reindeer Lake and back again. In 1937 the New England Museum of Natural History sponsored a solo trip by Downes to study the Eskimos of Boothia Peninsula, before which he made his way to Brochet at the north end of Reindeer Lake and investigated the histories, languages, and ways of the Crees and the Chipewyans. This fascination with northern Indians, and above all with the significance of dreams in their cultures, was central to Downes's travels. The Crees named him "The-man-who-talks-about-dreams." Two of Downes's unpublished writings are a Cree-Chipewyan dictionary and a volume titled "The Spirit World of the Northern Cree: Contributions to Cree Ethnology." The first of Downes's major canoe trips came in 1938, when he paddled alone from Waterways to Fitzgerald, after which he moved on the Great Slave, the Mackenzie, and Great Bear. . The Sleeping Island trip of 1939 - from Brochet to Nueltin Lake - was followed by another, less triumphant, venture into that region in 1940. Despondent as he was at his failure to reach ...